1996
DOI: 10.1128/jb.178.24.7047-7052.1996
|View full text |Cite
|
Sign up to set email alerts
|

Malate dehydrogenase from the mesophile Chlorobium vibrioforme and from the mild thermophile Chlorobium tepidum: molecular cloning, construction of a hybrid, and expression in Escherichia coli

Abstract: The genes (mdh) encoding malate dehydrogenase (MDH) from the mesophile Chlorobium vibrioforme and the moderate thermophile C. tepidum were cloned and sequenced, and the complete amino acid sequences were deduced. When the region upstream of mdh was analyzed, a sequence with high homology to an operon encoding ribosomal proteins from Escherichia coli was found. Each mdh gene consists of a 930-bp open reading frame and encodes 310 amino acid residues, corresponding to a subunit weight of 33,200 Da for the dimeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…One group includes cytoplasmic MDH, chloroplast MDH, and MDH from Thermus flavus; the other group includes MDHs that are similar to lactate dehydrogenase (LDH) (Naterstad et al, 1996). This review is a comprehensive overview of the properties, function, crystallization, and evolution of the microbial MDHs.…”
Section: Introductionmentioning
confidence: 99%
“…One group includes cytoplasmic MDH, chloroplast MDH, and MDH from Thermus flavus; the other group includes MDHs that are similar to lactate dehydrogenase (LDH) (Naterstad et al, 1996). This review is a comprehensive overview of the properties, function, crystallization, and evolution of the microbial MDHs.…”
Section: Introductionmentioning
confidence: 99%
“…A putative ribosome binding site (AGGA) is present 10 bp upstream of the translational start. Conserved residues known to bind substrate and participate in catalysis are found at Arg-83, Arg-89, Asp-149, Arg-152 His-176 and Ala-231 [11]. Residues 10^15 contain the glycine motif GXGXXG known to be characteristic of lactate dehydrogenases and the lactate-like Mdhs [12].…”
Section: Sequence Analysis Of Mdhmentioning
confidence: 99%
“…Crystallographic studies have shown that a charge imbalance inside the catalytic vacuole is responsible for substrate discrimination (Chapman et al ., 1999). Various data, based on the primary structure determination (Cendrin et al ., 1993; Naterstad et al ., 1996; Synstad et al ., 1996; Langelandsvik et al ., 1997), solution studies (Bonneté et al ., 1993), folding and association pathways (Madern et al ., 2000) and crystallographic studies (Richard et al ., 2000), have shown that, within the l ‐MalDH family, a lactate dehydrogenase‐like (LDH‐like) group of enzymes should be considered.…”
Section: Introductionmentioning
confidence: 99%